Ethical Sales Behavior Influencing Trust, Loyalty, Green Experience, and Satisfaction in UAE Public Entrepreneur Firms - Ahli, Marwa; Hilmi, Mohd Faiz; Abudaqa, Anas (Aptisi Transactions On Technopreneurship (ATT), 2024)
Customer satisfaction (CST) is a critical focus for both public and private organizations due to its significant impact on business success. In this context, ethical sales behavior, perceived trust, customer loyalty, and green experience are identified as key factors influencing CST. This study aims to examine the relationships among these variables within public sector organizations in the UAE. Primary data were collected from 224 respondents using a structured questionnaire. The data analysis was conducted utilizing descriptive statistics, multivariate assumptions, and a two-step approach that included both measurement and structural models. Structural equation modeling techniques were employed to test the relationships between the variables, grounded in the Resource-Based View (RBV) and expectation confirmation theory. The findings reveal that perceived trust, customer loyalty, and green experience significantly and positively impact customer satisfaction among public firms in the UAE. However, ethical sales behavior did not demonstrate a significant direct effect on customer satisfaction. These results provide valuable insights for policymakers and administrative representatives in the UAE public sector. To enhance customer satisfaction, it is recommended that public sector organizations prioritize building trust and loyalty while integrating green practices into their operations. Although ethical sales behavior does not directly affect customer satisfaction, it remains crucial for influencing trust and loyalty. The study underscores the importance of these factors in driving customer satisfaction and offers practical recommendations for public sector organizations aiming to improve their service quality and customer relations.